The Peculiarities of Teaching Foreign Languages by Means of Information and Communication Technologies - Shevchuk, Anna (Educational Challenges, 2021)
The paper investigates the peculiarities of teaching foreign languages by means of Information and Communication Technologies (ICT). In the course of a comprehensive study the most effective for the development of students’ linguistic and communicative competence, the following types of ICT were singled out and analysed: Internet-based project work, online correspondence by e-mail, chat, blogs, wikis and podcasts and training programs. The aim of the article is to identify the peculiarities of teaching foreign languages by means of ICT The theoretical, empirical and statistical methods have been used to reach the purpose. To check the effectiveness of applying ICT in teaching foreign languages empirical (diagnostic) methods such as testing, observation and discussion were used. The pedagogical experiment with the fourth-year students of Simon Kuznets Kharkiv National University of Economics was conducted. The pedagogical experiment showed the effectiveness of developing foreign language activity by means of ICT. The statistical methods helped to evaluate the results of the research. Using ICT is really helpful to increase students’ language competencies and, respectively, it provides the development of foreign language communicative competence in general. Conclusion: ICT creates a new environment and opportunities for foreign language acquisition; they have become an important educational tool successfully used in foreign language teaching.